(untitled) (Research, Society and Development, 2020)
Cagaita (Eugenia dysenterica DC.) plants are highly dependent on the micronutrient iron during their early development stages. Given this, we tested the hypothesis that initial seedling development is affected by a lack of specific micronutrients. We planted seedlings of this species in standard hydroponic solution, and in individual treatments, in which B, Cu, Fe, Mn, Zn or Mo were omitted. The development of symptoms of micronutrient deficiency in response to the different treatment solutions was monitored visually for 120 days after transplantation, and growth parameters and the content of different nutrients in the plant tissue were determined. The deficiency of the micronutrient Mo was the treatment with the greatest effect on seedling growth. The most commonly observed symptoms of nutrient deficiency were chlorosis and necrosis (Cu and Zn deprivation) and impaired root hair development (Fe and Cu deprivation). Overall, Fe was the micronutrient that accumulated most in the stems and roots of the seedlings exposed to the standard nutrient solution, which confirms the importance of the availability of this nutrient in the initial stages of seedling development for the production of healthy cagaita plants, with greater viability.